Search Strategy for Improving documentation of sexual orientation and gender identity in pediatric primary care: a Scoping Review - Myers-Kelley, Soph (My University, 2022)
A scoping review search concerning SOGI (sexual orientation and gender identity) in pediatric primary care
Keywords: primary care; sexual orientation; gender identity; pediatrics; search hedge; expert review